Efforts to Form Sakinah Families for User Clients Drug Rehabilitation Houses in East Java - Hawa Hidayatul Hikmiyah (NUSANTARA: Journal Of Law Studies, 2023)
Drug abuse is important, dynamic and complex to handle. This is proven by data from the National Narcotics Agency (BNN), the number of drug cases that have been handled by the responsible parties, cases included in the handling is 43,657 cases, North Sumatra has the most cases with 6,285 cases, 5,237 cases are in Jakarta and East Java—third place with the highest number of drug use cases, namely 4,752 cases. The type of research used is field research. Namely, this research is field research to obtain objective, actual and robust data. This type of research is carried out to deal with cases in the field growing in the community. Based on the Qur'an, Surah ar-Rum verse 21 indirectly contains the meaning of sakinah, which means peace. There are different meanings, but they contain the same meaning, namely sakinah, which can be interpreted as harmony, or it can also be called peace and comfort. Referring to what has been stated above, a common thread can be drawn: sakinah means a family in which there is something comfortable, peaceful, and calm both physically and mentally.